The Influence of Actual Usage in Using QRIS on Payment Methods - Sefrika, S (IJISTECH (International Journal of Information System and Technology), 2023)
Along with technological developments, one of the features used by many users is electronic money. QRIS as an electronic payment method is currently widely used by citizens to carry out payment transactions. However, more in-depth research needs to be done to find out the factors that influence the use of QRIS. This research aims to determine the background that underlies users in using the QRIS method. This research method uses the Technology Acceptance Model or TAM. TAM is a method that can be used to find out how technology is accepted by users with valid measurement results. The research results show that the majority of users use the QRIS payment method because of the perception of convenience, thereby generating interest among users